First measurement of Λc+ production down to pT=0 in pp and p -Pb collisions at sNN =5.02 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; et al. (American Physical Society, 2023)
The production of prompt ${\mathrm{\ensuremath{\Lambda}}}_{c}^{+}$ baryons has been measured at midrapidity in the transverse momentum interval $0<{p}_{T}<1 \text{GeV}/c$ for the first time, in $pp$ and $p$--Pb collisions at a center-of-mass energy per nucleon-nucleon collision $\sqrt{{s}_{NN}}=5.02\phantom{\rule{0.16em}{0ex}}\text{TeV}$. The measurement was performed in the decay channel ${\mathrm{\ensuremath{\Lambda}}}_{c}^{+}\ensuremath{\rightarrow}p{K}_{S}^{0}$ by applying new decay reconstruction techniques using a Kalman-Filter vertexing algorithm and adopting a machine-learning approach for the candidate selection. The ${p}_{T}$-integrated ${\mathrm{\ensuremath{\Lambda}}}_{c}^{+}$ production cross sections in both collision systems were determined and used along with the measured yields in Pb--Pb collisions to compute the ${p}_{T}$-integrated nuclear modification factors ${R}_{p\mathrm{Pb}}$ and ${R}_{AA}$ of ${\mathrm{\ensuremath{\Lambda}}}_{c}^{+}$ baryons, which are compared to model calculations that consider nuclear modification of the parton distribution functions. The ${\mathrm{\ensuremath{\Lambda}}}_{c}^{+}/{D}^{0}$ baryon-to-meson yield ratio is reported for $pp$ and $p$--Pb collisions. Comparisons with models that include modified hadronization processes are presented, and the implications of the results on the understanding of charm hadronization in hadronic collisions are discussed. A significant ($3.7\ensuremath{\sigma}$) modification of the mean transverse momentum of ${\mathrm{\ensuremath{\Lambda}}}_{c}^{+}$ baryons is seen in $p$--Pb collisions with respect to $pp$ collisions, while the ${p}_{T}$-integrated ${\mathrm{\ensuremath{\Lambda}}}_{c}^{+}/{D}^{0}$ yield ratio was found to be consistent between the two collision systems within the uncertainties.
Keywords: Physics; Baryon; Hadronization; Particle physics; Lambda; Hadron; Energy (signal processing); Production (economics); Nuclear physics; Quantum mechanics; https://purl.org/pe-repo/ocde/ford#1.03.03